Using a qualitative co-design approach to identify recommendations for improving access to medication reviews for people from ethnic minority communities. (30th November 2022) - Robinson-Barella, A; Sile, L; Govind, T; Guraya, H K; O'Brien, N; Harris, V; Pilkington, G; Todd, A; Husband, A
Abstract: Introduction: Reviews of medication are vital to support medicine effectiveness and optimise person-centred care outcomes. However, inequalities negatively impact ethnic minority populations when accessing medicine review services. 1 It is important to identify opportunities to improve access for these communities. Previous studies have demonstrated the significance of overcoming accessibility barriers, but specific detail about how best to achieve this is lacking. 2, 3 Through co-design workshops, this study seeks to integrate the voices of those people from ethnic minority populations to gain better insight into improving access to medicines review services for ethnic minority communities. Aim: This qualitative, person-centred co-design study sought to build greater knowledge and understanding by involving representatives from communities whose needs may remain unmet. When considering the value that medication reviews can offer in optimising a person's medication, this study aimed to: (i) better understand existing barriers that may impact those from ethnic minority communities when accessing services and to (ii) identify measures that may facilitate improved service accessibility for these groups. Methods: A series of co-design workshops, with four groups of patient-stakeholders, were conducted between September-November 2021; they took place in-person or via video call whilst adhering to COVID-19 restrictions. Existing evidence-based perceptions affecting access to medicines services were critiqued and recommendations were generated to improve access for ethnic minority patients. The workshops were audio-recorded and transcribed verbatim to enable thematic analysis. QSR NVivo (Version 12) facilitated data analysis. The Health Research Authority granted ethical approval (ref: 21/HRA/1426). Results: Twelve participants were recruited: including 8 UK citizens, 2 asylum seekers and 2 participants in receipt of residency visas. In total, 4 different ethnic minority groups were represented. Each participant took part in a first and second workshop to share and co-create recommendations. Three recommendations were developed and centred on: (i) delivering culturally competent medicines review services; (ii) building awareness of medicines review services and how to access them; and (iii) enabling better discussions with patients from ethnic minority communities. Discussion/Conclusion: The results have important implications for overcoming ethnic inequalities in access to medicines reviews. The data highlighted the significance of raising awareness of the medicine review services and understanding each person's lived experiences in order to address barriers that currently affect access. Delivering medication review services with cultural competency is vital; steps should be taken to address potential language barriers and build patient-provider relationships through in-person medication reviews. Collaborative co-production approaches could enable better design, implementation and delivery of medication services that are accessible and culturally competent, in order to best meet the needs of ethnic minority communities. Steps should be taken to address knowledge gaps around cultural competence training to enable the creation of pharmacies as inclusive, person-centred healthcare settings. Methods for improving person-centred communication within pharmacies should be further explored. Close, collaborative working with individual populations could enable specific tailoring of medicines review services that best meet the needs of the community. The National Institute for Health Research Applied Research Collaboration (NIHR ARC) and Newcastle University Patient and Public Involvement and Engagement group had extensive input in the study design and conceptualisation. Seven patient champions were appointed to the steering group to ensure that the research was conducted, and the findings were reported, with cultural competence and sensitivity. References: 1. Robinson A, et al . A qualitative exploration of the barriers and facilitators affecting ethnic minority patient groups when accessing medicine review services: perspectives of healthcare professionals. Health Expectations, 2021. DOI: 10.1111/hex.13410. 2. Robinson A, et al. " He or she maybe doesn't know there is such a thing as a review": a qualitative investigation exploring barriers and facilitators to accessing medication reviews from the perspective of people from ethnic minority communities. Health Expectations, 2022. DOI: 10.1111/hex.13482. 3. Latif A, et al . A qualitative exploration to understand access to pharmacy medication reviews: views from marginalized patient groups. Pharmacy, 2020. DOI: 10.3390/pharmacy8020073.